Tickborne Relapsing Fever in Israel - Sidi, Gil (Centers for Disease Control and Prevention, 2005)
We evaluated the epidemiology of relapsing fever from 1971 to 2003 in Israel. In civilians, incidence declined from 0.35 to 0.11 cases per 100,000 persons annually; in military personnel it averaged 6.4 cases per 100,000 persons annually. These data imply that the pathogen and vector continue to exist in Israel.